AMAZON'S STEP TOWARDS CLEAN ENERGY AND ITS IMPACT ON THE USA - Fitri Silaban; Puan Maharani Putri Admoko; Sartika Laurenvia Yohana; Veryzal (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
Amazon is an American company that is based in Seattle. This company deals in e-commerce, it's the largest internet-based store and is owned by Jeff Bezos. The company was founded on July 5, 1994. With Amazon committed to a climate pledge, this means amazon has the responsibility to make a change towards the environment and the world Amazon purchases renewable energy outside of the current grid mix to promote the production and creation of new renewable energy. These sources were diverse in order to collect enough information: books, journals, and websites were all included in the creation of this text. Since we used to be able to comprehend sentences and perceptions, we use qualitative research analyst approaches to collect data. Renewable energy comes from naturally restoring yet flow-limited sources. Renewable resources are basically limitless in terms of duration but have a finite quantity of energy per amount of time. Amazon has a huge impact on the economy in the US. With the many investments that Amazon has made for the development of its own employees and unfortunate children.According to the North Carolina sustainable energy association Clean energy includes both renewable energy and energy saved through energy efficiency measures. And with Amazon and Tesla being US-based companies this will make the U.S seen as a country with advanced technology and also become advanced and foremost in terms of politics of energy. Keywords: Amazon, clean energy, Jeff Bezos, renewable energy